Epidemiologic trends and survival of early-onset gastroenteropancreatic neuroendocrine neoplasms - Yao, Hailing; Hu, Gengcheng; Jiang, Chen; Fan, Mengke; Yuan, Lanlai; Shi, Huiying; Lin, Rong (Frontiers in Endocrinology, 2023)
Background: The epidemiologic trends and survival related to early-onset gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) have not been well explored. Methods: Trends in the incidence and incidence-based mortality of early-onset GEP-NENs between 1975 and 2018 were obtained from the Surveillance, Epidemiology, and End Results database, and were stratified by age, sex, race, tumor site, stage, and grade. Associated population data were used to determine overall survival and independent prognostic factors for patients with early-onset GEP-NENs. Results: A total of 17299 patients diagnosed with early-onset GEP-NENs were included in this study. Results revealed an increase in the incidence (5.95% per year, 95% confidence interval (CI), 5.75-6.14%) and incidence-based mortality (4.24% per year, 95% CI, 3.92-4.56%) for early-onset GEP-NENs from 1975 to 2018, with higher rates of increase (4.45% per year, 95% CI, 4.38-4.53) than those of later-onset GEP-NENs (4.13% per year, 95% CI, 3.89-4.37). Increases in incidence were observed across all age, races, tumor sites, grades, and stages, except for patients with unknown stage. Compared to those with later-onset GEP-NENs, a higher proportion of female gender (54.5% vs. 49.0%, p <0.001), well-differentiated tumor (31.1% vs. 28.0%, p <0.05), and localized disease (55.2% vs. 46.7%, p <0.05) were observed in the cohort of patients with early-onset GEP-NENs. Moreover, early-onset GEP-NENs exhibited a superior overall survival in comparison to later-onset GEP-NENs, irrespective of tumor site, grade, or stage (p <0.0001). Multivariable survival analysis identified that race, marital status, stage, grade, chemotherapy, and primary site were significantly correlated with OS in individuals with early-onset GEP-NENs. Conclusions: The incidence and incidence-based mortality rates of early-onset GEP-NENs have steadily increased over time, with higher rates of increase than those of later-onset GEP-NENs. The clinical characteristics and survival were different between early-onset and later-onset GEP-NENs groups. Race, marital status, stage, grade, chemotherapy, and primary site were independent prognostic factors for early-onset GEP-NENs. Further investigations are warranted to better understand the characteristics of this disease subgroup.